Semi-Industrial Production of Kashkaval of Pindos Cheese Using Sheep or a Mixture of Sheep–Goat Milk and Utilization of the Whey for Manufacturing Urda Cheese - Pappa, Eleni C. (Foods, 2020)
Kashkaval of Pindos cheese was successfully produced using 100% sheep milk (KS) or with the addition of 10% goat milk (KG). Urda cheese was manufactured using 100% sheep (US) or 90% sheep–10% goat (UG) whey from the production of kashkaval of Pindos cheese. Both cheeses were made taking into account their traditional cheese-making methods. The cheeses were assessed for their chemical, microbiological and organoleptic characteristics. Generally, no significant differences were observed between KS and KG cheese and between US and UG cheese regarding their physicochemical, textural characteristics, soluble nitrogen fraction and total fatty acid content. The fat content of Urda cheese was low, in accordance with the demand of consumers for healthy products. KS cheeses showed higher total volatile compounds than KG cheeses at 60 and 90 days of ripening and storage as well as lower counts of thermophilic–mesophilic lactic acid bacteria. No differences were observed in the microbial counts between US and UG cheeses. Acetone, hexanal, 2 heptanone, ethanol and toluene were found in abundance in Urda cheeses. Both kashkaval of Pindos and Urda cheeses received high scores during the organoleptic evaluation. The obtained data may lead to the production of both cheeses with standard characteristics according to the traditional recipes and improve their recognition.